Pengaruh Tingkat Pendidikan dan Kemiskinan Terhadap Pertumbuhan Ekonomi Di Provinsi DKI Jakarta Periode 2017-2021 - Nadila Nadila (Universitas 45 Surabaya, 2023)
This study aims to analyze the effect of education and poverty levels on economic growth in DKI Jakarta Province in the 2017-2021 period. This study used VECM analysis. Based on the results of the analysis, the variable level of education has a negative and significant influence on economic growth in DKI Jakarta province, while the variable poverty rate has a positive and insignificant influence on economic growth in DKI Jakarta province. Furthermore, on stationary tests the variables of education level, poverty and economic growth have been stationary at the first difference level. The results of long-term estimates that the variable poverty rate in DKI Jakarta Province in the 2017-2021 period, has an effect and is significant on lag one at a real level of 5%. Thus the poverty rate has a dominant effect on economic growth